Body composition and risk of major gynecologic malignancies: Results from the UK Biobank prospective cohort - Peng Yun; Bin Xia; Xiao‐hui Tian; Ting Gong; An‐ran Liu; Jin‐qiu Yuan; Fang‐ping Li (Cancer Medicine, 2021)
Abstract Objective To evaluate the association between body composition and subsequent risk of the major gynecologic malignancies. Methods This is a prospective analysis of participants from the UK Biobank. We measured baseline body composition and confirmed cancer diagnosis through linkage to cancer and death registries. We evaluated hazard ratios (HRs) and confidence interval (CIs) with COX models adjusting for potential confounders. Results We document 1430 cases of the top three gynecologic malignancies (uterine corpus cancer 847 cases, ovarian cancer 514 cases, and cervical cancer 69 cases) from 245,084 female participants (75,307 were premenopausal and 169,777 were postmenopausal). For premenopausal women, whole body fat‐free mass (WBFFM) was associated with an increased risk of uterine corpus cancer (Adjusted HR per unit increase 1.04, 95% CI 1.02–1.06). For postmenopausal women, compared with the first quartile, the fourth quartile of WBFFM and whole body fat mass(WBFM) was associated with 2.16 (95% CI 1.49–3.13) times and 1.89 (95% CI 1.31–2.72) times of increased uterine corpus cancer risk, respectively. Regarding the distribution of body fat mass (FM)/fat‐free mass (FFM), FFM distributed in the trunk was associate with increased uterine corpus cancer risk in premenopausal (HR 1.18,95% CI 1.07–1.31) and postmenopausal women (HR 1.13,95% CI 1.09–1.18). Meanwhile, FM/FFM distributed in the limbs present an U‐shaped associations with uterine corpus cancer risk. We did not observe any association between aforementioned body composition indices with ovarian or cervical cancer. Conclusion FM is associated with an increased risk of uterine corpus cancer in postmenopausal women. Meanwhile, FFM is found to be a risk factor for uterine corpus cancer in both premenopausal and postmenopausal women. No association of body composition with ovarian or cervical cancer was observed.